Job Satisfaction of Employees Working in Nepalese Private College - Mishra, Sanjib; Shrestha, Rita (Nepal Journal of Multidisciplinary Research, 2019)
Employees are the major elements of organizational performance so every employee should be well-satisfied at work. Satisfaction indicates the happiness, fulfilling their desires and needs at work. The main objective of this study was to explore the employee satisfaction in the academic institutions of Nepal. The study had collected the data from teaching and non-teaching staffs of academic institutions. There were 43 respondents participated in the study. Simple random sampling technique was adopted to select the respondent. The structured survey questionnaire was used for data collection. The standard scale developed by Wellness Council of America (WELCOA) was used to measure the level of satisfaction. The result shows that in total, 67.4% employee had reported ‘Great Job’, 27.9% reported ‘Good job’ and 4.7% reported ‘Ok job’. It indicates that majority of employees were highly satisfied with their job in academic sector. It is good to know that Nepalese academic sectors are growing day by day by adopting the high-technology, new management system, participatory approach, motivational activities so that employees are also well-satisfied with the working environment, salary and incentive, capacity building training, promotion and exposure programs. The further research can explore the effect of organizational climate and employee satisfaction in Nepalese Private college.